Yiqifumai injection and its main ingredients attenuate lipopolysaccharide‐induced cerebrovascular hyperpermeability through a multi‐pathway mode. (21st July 2019) - Li, Dan‐Tong; Sun, Kai; Huang, Ping; Pan, Chun‐Shui; Yan, Li; Ayan, Ayididaer; Liu, Yu‐Ying; Fan, Jing‐Yu; Fang, Wei‐Gang; Han, Jing‐Yan
Abstract: Objective: Yiqifumai injection is a compound Chinese medicine used to treat microcirculatory disturbance‐related diseases clinically. Our previous study proved that Yiqifumai injection pretreatment inhibited lipopolysaccharide‐induced venular albumin leakage in rat mesentery. This study aimed to investigate whether Yiqifumai injection attenuated cerebral microvascular hyperpermeability and corresponding contribution of its main ingredients. Methods: Rats were challenged by lipopolysaccharide infusion (5 mg/kg/h) for 90 minutes. Yiqifumai injection (160 mg/kg/h), Rb1 (5 mg/kg/h), Sch (2.5 mg/kg/h), and Rb1 (5 mg/kg/h) + Sch (2.5 mg/kg/h) were infused 30 minutes before (pretreatment) or after (post‐treatment) lipopolysaccharide administration. Results: Both pretreatment and post‐treatment with Yiqifumai injection attenuated cerebral venular albumin leakage during lipopolysaccharide infusion and cerebrovascular hyperpermeability at 72 hours after lipopolysaccharide infusion. Yiqifumai injection restrained the decreased junction protein expression, adenosine triphosphate content, and mitochondria complex I, II, IV, and V activities. Moreover, Yiqifumai injection inhibited toll‐like receptor‐4 expression, Src phosphorylation, and caveolin‐1 expression. Its main ingredients Rb1 and Sch alone worked differently, with Rb1 being more effective for enhancing energy metabolism, while Sch attenuating toll‐like receptor‐4 expression and Src activation. Conclusion: Yiqifumai injection exerts a protective and ameliorated effect on cerebral microvascular hyperpermeability, which is more effective than any of its ingredients, possibly due to the interaction of its main ingredients through a multi‐pathway mode.